The Role of Bio, Organic and Chemical Fertilizers in Enhancing Induced Resistance of Fig Trees (Ficus Carica L.) Against the Fig Wax Scale (Ceroplastes Rusci L.) - Al-Abadi, Ruqaya S.; Al-Obaidy, Shaymaa H. (American Journal of Botany and Bioengineering, 2025)
A field study was conducted in Bani Muslim village, Babylon Governorate, during the 2024 growing season to evaluate the efficacy of three fertilizer types (bio-, organic, and chemical) and two application methods (foliar application and soil addition) in inducing systemic resistance in fig trees (Ficus carica L.) against the fig wax scale, Ceroplastes rusci L. The study assessed biochemical resistance indicators—specifically Jasmonic Acid (JA), Peroxidase (PO), and Polyphenol Oxidase (PPO)—and their correlation with pest mortality rates. Results demonstrated that organic treatments (Humic acid and Compost) were significantly superior, recording the highest concentrations of defensive compounds (97.5 ppm for JA and 90.4 ppm for PPO). This biochemical enhancement resulted in the highest mortality rates for both nymphs (93.70%) and adults (77.00%). Bio-fertilizers (Bacillus amyloliquefaciens) followed in efficacy, whereas chemical fertilizers (NPK) exhibited the lowest efficacy. These findings suggest that organic and biofertilizers can be integrated as effective components in Integrated Pest Management (IPM) programs for fig orchards to enhance host plant resistance.